Some studies of the interaction between N-two level atoms and three level atom - D.A.M. Abo-Kahla; M.M.A. Ahmed (Journal of the Egyptian Mathematical Society, 2016)
In this paper, we present the analytical solution for the model that describes the interaction between a three level atom and two systems of N-two level atoms. The effect of the quantum numbers on the atomic inversion and the purity, for some special cases of the initial states, are investigated. We observe that the atomic inversion and the purity change remarkably by the change of the quantum numbers.